Good practices: experiences and challenges- Unsam, Argentina - José Barbero; Tamara Werhun Chomik; Lovisa Ericson; Daniel Alvarez (Universitas Diponegoro, 2022)
The impact of university activities on the environment should be studied and managed based on the constant evaluation of real consumption needs, on the use of reusable or recyclable resources and on the encouragement of an active and participatory role in terms of care and improvement of the environment (physical and social) through responsible use. This is a challenge that requires the commitment of the entire university and involves a continuous process of awareness-raising among students, teachers, researchers and staff. In 2016, UNSAM the National University of San Martin (Universidad Nacional de San Martín) conducted a study on mobility in its main campus